1982
DOI: 10.1093/carcin/3.6.657
|View full text |Cite
|
Sign up to set email alerts
|

Strand breakage and decreased molecular weight of DNA induced by specific metal compounds

Abstract: The effect of various metal compounds on the DNA of Chinese hamster ovary (CHO) cells was studied. Both NiCl2 and crystalline NiS caused DNA strand breaks in cultured CHO cells, whereas amorphous NiS did not. Strand breaks were quantitated by determining the number of average molecular weight of DNA following treatment with the metal compounds. Exposure of cells to crystalline NiS, CoS, CdS, AgS, CuS and Ni3S2 at 10 micrograms/ml for 24 h also induced DNA strand breaks. Similar exposure to activated charcoal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
3

Year Published

1991
1991
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(32 citation statements)
references
References 0 publications
1
28
0
3
Order By: Relevance
“…cad mium [1], cobalt [2], mercury [3], nickel [4] and arsenic [5]. There is evidence that the genotoxic action of Cd, Co, Hg and Ni may be mediated by oxygen free radicals from auto-oxidative processes in the cells induced by the metal compounds [3,6,7], In previous studies trivalent arsenic has been found to induce chromosome aber rations and sister chromatid exchanges (SCEs) in human cells [5,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…cad mium [1], cobalt [2], mercury [3], nickel [4] and arsenic [5]. There is evidence that the genotoxic action of Cd, Co, Hg and Ni may be mediated by oxygen free radicals from auto-oxidative processes in the cells induced by the metal compounds [3,6,7], In previous studies trivalent arsenic has been found to induce chromosome aber rations and sister chromatid exchanges (SCEs) in human cells [5,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…From these studies and others it is evident that the silver ion does bind with DNA in solution in vitro, and that it can interact with DNA in ways that cause DNA strand breaks and affect the fidelity of DNA replication (Goff and Powers 1975;Loeb et al 1977;Luk et al 1975;Mauss et el. 1980;Robison et al 1982;Scicchitano and Pegg 1987). However, silver has not been found to be mutagenic in bacteria (Demerec et al 1951;Kanematsu et al 1980;McCoy and Rosenkranz 1978;Nishioka 1975;Rossman and Molina 1986).…”
Section: Genotoxic Effectsmentioning
confidence: 99%
“…Silver is not mutagenic in bacteria but it has been found to cause DNA damage in mammalian cell culture (Robinson, Cantoni, and Costa 1982). No studies were located regarding cancer in humans or animals following oral, inhalation or dermal exposure to silver or silver compounds (ATSDR 1990).…”
Section: Genotoxicitymentioning
confidence: 99%